Ethylene emitted by viral pathogen-infected pepper (Capsicum annuum L.) plants is a volatile chemical cue that attracts aphid vectors - Kwon, Sun-Jung; Han, Soo-Jung; Kim, Myung-Hwi; Jang, Seok-Yeong; Choi, Ji-Soo; Seo, Jang-Kyun (Frontiers in Plant Science, 2022)
Plant viruses are obligate intracellular pathogens, and most depend on insect vectors for transmission between plants. Viral infection causes various physiological and metabolic changes in host traits, which subsequently influence the behavior and fitness of the insect vectors. Cucumber mosaic virus (CMV), one of the most widespread pathogens in pepper (Capsicum annuum L.), is transmitted by aphid vectors in a non-persistent manner. Here, we examined whether CMV infection in pepper affects the behavior of aphid vectors (Myzus persicae and Aphis glycines) in pepper. Aphid preference test revealed that significantly more aphids were attracted to CMV-infected pepper plants than to healthy plants. Comparative transcriptome analysis revealed a significant activation of the ethylene biosynthesis pathway in CMV-infected pepper plants. Indeed, gas chromatography analysis demonstrated that ethylene emission was significantly increased by CMV infection in pepper plants. Elevated ethylene emission in ethephon-treated healthy pepper increased their attractiveness to aphids. In contrast, aphid preference decreased after chemical inhibition of ethylene biosynthesis in CMV-infected pepper plants. Our results suggest that the ethylene emitted by CMV infection is a volatile cue that regulates the attractiveness of pepper plants to M. persicae and A. glycines.